Impact of non-high-density lipoprotein cholesterol in mortality and cardiovascular events among middle-aged Russian men: 40 years ago and now - S. A. Shalnova; A. E Imaeva; Yu. A Balanova; V. A Kutsenko; A. V Kapustina; V. A Metelskaya; N. A Imaeva; B. M Nazarov; O. E Ivlev; E. B Yarovaya; O. M Drapkina (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the non-high density lipoprotein cholesterol (non-HDL-C) predictive ability in relation to cardiovascular events, all-cause and cause-specific mortality and among middle-aged Russian men now and 40- years ago.Material and methods. For analysis data from 9507 men aged 35-64 without cardiovascular disease (CVD) who did not receive lipid-lowering therapy, participants of two independent population prospective cohort studies — 40-year retrospective (Russian LRC) and conducted at the present time (ESSE-RF) — were used. In the analysis, all-cause mortality, cancer and CVD mortality, and non-fatal CVD (myocardial infarction and STEMI stroke) were assessed. The follow-up period for the LRС study was 10 years, and for the ESSE-RF study, it was 7.8 years.Results. The mean value of non-HDL-C was 0.3 mmol/L higher among participants from the Russian LRC cohort than among men from the ESSE-RF cohort. Low non-HDL-C levels were associated with an increased risk of all-cause mortality. A strong link between high levels of non-HDL-C and the development of fatal and nonfatal CVD events was also found in both cohorts. Men with non-HDL-C levels ≥4.5 mmol/L in the LRC study and ≥4.2 mmol/L in the ESSE-RF study had a significantly increased risk of fatal and non-fatal CVDs (63% and 27%, respectively) and decreased risk of cancer mortality (28% and 50%, respectively). Conclusion. Downwards trends in non-HDL-C levels over the past 40 years were indicated. The study identified a decline of non-HDL-C in the general population level since the 1970s of the 20th century. Up to the present time, there is still a non-linear relationship between the level of non-HDL-C and total mortality, that could be explained by the presence of differently directed associations between this parameter, cancer mortality and the development of fatal and non-fatal CVDs.